PENGARUH PROFITABILITY, KEPEMILIKAN INSTITUSIONAL, FIRM SIZE, DAN LIQUIDITY TERHADAP TAX AVOIDANCE - Gui, Andreas; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study iss to analyze the effect of profitability, institutional ownership, firm size, and liquidity on tax avoidance for 2019-2021. The data used in this study are from industry companies listed on the Indonesia Stock Exchange using SPSS version 25. This study uses quantitative research using secondary data with a purposive sampling method involving 45 industry companies as research samples. The results of this study conclude that profitability and institutional ownership significantly affect tax avoidance, while firm size and liquidity have no significant impact on tax avoidance.